Payroll Information System for SMP PGRI 16 Sidoarjo - Dimas Sya’aldi Pasa; Ade Eviyanti; Sumarno Sumarno (Procedia of Engineering and Life Science, 2022)
A salary is a form of result in the form of money or goods given to individuals or groups. The payroll calculation system process that is currently running is still using the Microsoft Excel application. But now everything has developed rapidly, and with the existence of information technology, everything can be done more efficiently. Information technology has now grown very far and has begun to be widely applied by anyone and in any case, including the payroll system. The application of information technology to payroll can increase the effectiveness of the treasurer's performance in a school. SMP PGRI 16 Sidoarjo is one of the agencies that has not implemented information technology in the payroll sector, it became the basis for the formation of this information system.